Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1074/jbc.m114.631705
|View full text |Cite
|
Sign up to set email alerts
|

Human CLC-K Channels Require Palmitoylation of Their Accessory Subunit Barttin to Be Functional

Abstract: Background: CLC-K channels and their subunit barttin are crucial for urinary concentration and hearing. Results: Non-palmitoylated barttin mutants reduce CLC-K current amplitudes without modifying unitary channel properties. Conclusion: Palmitoylation of barttin switches CLC-K channels into an active state. Significance: Palmitoylation/depalmitoylation of CLC-K/barttin channels pre-inserted in epithelial plasma membranes might regulate renal chloride absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 53 publications
9
28
0
Order By: Relevance
“…Altogether, the above-mentioned results (i.e., Figs 2, 3 and S3) are in line with our previous observation that non-palmitoylated barttin did not reduce surface membrane insertion of ClC-K/barttin, but selectively impaired activation of the channel complex (8).…”
Section: Knockdown Of Dhhc7 Reduces Activation Of Hclc-ka/barttin Chasupporting
confidence: 92%
See 3 more Smart Citations
“…Altogether, the above-mentioned results (i.e., Figs 2, 3 and S3) are in line with our previous observation that non-palmitoylated barttin did not reduce surface membrane insertion of ClC-K/barttin, but selectively impaired activation of the channel complex (8).…”
Section: Knockdown Of Dhhc7 Reduces Activation Of Hclc-ka/barttin Chasupporting
confidence: 92%
“…S3D). The results confirmed the wellknown barttin function of promoting ClC-Ka insertion into the plasma membrane (8). More importantly, manipulation of barttin palmitoylation via DHHC7 overexpression or knockdown did not result in any visible changes in the distribution of the ClC-Ka/barttin complex in MDCKII cells (Figs S3C,D).…”
Section: Dhhc7 Is a Palmitoyl Acyltransferase For Barttin -supporting
confidence: 85%
See 2 more Smart Citations
“…Several disease-causing mutations in the cytosolic amino terminus of barttin lack activation of CLC-K channels upon co-expression (26). Recently, it was shown that cysteines at positions 54 and 56, located immediately after the second transmembrane domain of barttin, must be palmitoylated for the activation of CLC-K channels (29). These findings might support a possible interaction of the CBS2 domain of ClC-Kb with the cytosolic amino acids close to the transmembrane core (61).…”
Section: Discussionsupporting
confidence: 56%